HIMPUNAN DOA PELITA HATI DALAM SOROTAN DOKUMEN GEREJA TENTANG LITURGI DAN DEVOSI - Antonio Camnahas (Institut Filsafat dan Teknologi Kreatif Ledalero, 2011)
In the face of the rapid expansion of prayer groups, the question arises as to the spiritual identity of this phenomenon. How far are they authentic or perhaps even heretical? This essay studied such a prayer group and aims to answer the question – authentic or heretical? - in the light of the official teaching of the Catholic Church concerning devotion and religious practices. Through such a study people should not be too quick to classify such groups as marginal or even un-Catholic, or conversely, too easily defend and justify their existence and practice. Prayer groups can offer “grace” but also potentially insert a “curse” into the life of their adherents. That is why church authority needs to be seriously concerned with such developments. If guided adequately, prayer groups can offer much to the development of the peoples’ faith. Conversely, if they are not correctly guided, prayer groups can potentially lead people up the wrong path. This empirical study helps us to evaluate such groups critically. Keywords: kelompok doa, hamba Tuhan, ilham, devosi, kesalehan umat, praktek penyembuhan, kesaksian, otoritas gerejani.